Contrastive Analysis between Indonesian and English Declarative Sentences - Adiantika, Hanif Nurcholish (ELT in Focus, 2020)
The issue of English acquisition in Indonesian context where English is taught as a foreign language has been circulating for years. The presents study aims at contrasting two languages as, Indonesian language as the Source Language (SL) and English as the Target Language (TL). Participants were chosen purposively and generated 10 students of Senior High School. Data were collected through written test. The researcher provides 21 Indonesian declarative sentences as the main instrument. The result of this research was initiated qualitatively. The findings of the study indicate that the similarities of declarative sentence patterns between Indonesia and English language revealed in three categories. They are transitive, bitransitive, and intransitive. Furthermore, the differences are indicated by four categories, those are nominal, adjectival, prepositional, and numeral category. The presents study suggests to initiate the study of contrastive analysis in different languages to obtain deeper understanding and horizon about the language.